DESAIN APLIKASI MOBILE PANDUAN SHOLAT DAN DOA UNTUK ANAK GANGGUAN PENDENGARAN - Robi'in, Bambang; Tyas, Zahra Arwaning (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2018)
Children with hearing loss are children who experience learning difficulties. They have limited vocabulary and language in communication that hampers the learning process. They need a special way of learning and are usually educated in special schools. Level 2 elementary students at SLB B Karnnamanohara have difficulty learning prayer and daily prayer. Almost all elementary level 2 students cannot pronounce daily prayers and prayers. They need interesting learning resources and according to their characteristics. This study aims to design multimedia mobile application of prayer and daily prayers guides for children with hearing loss. The research method consists of five stages: data collection, data analysis, storyboard making, prototype design, and prototype evaluation. This research has been designed to multimedia mobile applications of prayer and prayers guides for children hearing impairments according to the needs of users who have different characteristics with users in general. The results showed that the prototype design of the multimedia mobile application prayer and prayer daily guides for children with hearing loss had met the needs of users with evaluation values of 4.42 from a scale of 5.